Feasibility and Safety of the Distal Transradial Artery for Coronary Diagnostic or Interventional Catheterization - Yaowang Lin; Xin Sun; Ruimian Chen; Huadong Liu; Xinli Pang; Jie Chen; Shaohong Dong (Journal of Interventional Cardiology)
Background. This prospective study compared the success rate and safety of a distal transradial artery (dTRA) approach to that of the conventional transradial artery (TRA) for coronary angiography or percutaneous coronary intervention. Methods. From January 2019 to April 2020, nine hundred consecutive patients (height < 190 cm) scheduled for coronary angiography or percutaneous coronary interventions were randomly and equally assigned to receive either dTRA or conventional TRA catheterization. Results. Successful access was achieved in 96.00% and 96.67% of the dTRA and conventional TRA groups, respectively (P=0.814). Compared with the TRA group, patients in the dTRA experienced significantly less hemostatic band removal time (150.5 ± 50.5 cf. 210.6 ± 60.5 min, P=0.032); minor bleeding of the access site (2.44% cf. 6.44%, P=0.038); hemostatic band cost (USD; 0.1 cf. 59.4, P=0); and postprocedural radial artery occlusion (1.56% cf. 3.78%, P=0.035). A lower body mass index was a higher risk factor for dTRA access failure (odds ratio = 0.79, P=0.024), with a cutoff of 22.04 kg/m2. Conclusion. Compared to conventional TRA, dTRA had a comparable high success rate, with fewer associated complications. Clinicians should use the dTRA with caution in patients with low body mass index.